Tendon Transfers in Foot Drop - Krishnamurthy, Sridhar; Ibrahim, Mohamed (Indian Journal of Plastic Surgery, 2019)
The common peroneal nerve is the most commonly injured nerve in the lower extremity. Peroneal nerve pathology results in loss of dorsiflexion at the tibiotalar joint, loss of eversion at the subtalar joint, and loss of extension of toes resulting in foot drop. The varied etiology of the problem is discussed. The various treatment modalities like conservative management, steroid therapy, nerve decompression, nerve repair, or reconstruction are described, but due to uncertain outcomes after primary nerve procedures, secondary procedures like tendon transfers often end up as definitive treatment. The rationale and technique of tibialis posterior transfer is discussed in detail.
Keywords: foot drop; tibialis posterior transfer; tendon transfer for foot drop